Comparison of Zinc ( Zn ) and Cadmium ( Cd ) Levels in Rhizophora Mangrove Species mucronata in Muara Tukad Badung, Bali - Ferdinan, David Firman; Darmadi, Anak Agung Ketut; As-syakur, Abd. Rahman; Wijana, Made Sara (Bumi Lestari; Vol 24 No 2 (2024), 2024)
Mangrove forests are an ecosystem that has an important role and function for the environment. Mangrove forests have ecosystems that are very beneficial to humans directly or indirectly. Apart from that, the mangrove ecosystem also has other important functions, namely as a catcher of sediment and as a prevention of erosion and as a soil stabilizer in estuary areas. Data collection was carried out in March using several methods, namely BCF, TF, and Igeo. Sampling was carried out using the Rhizopora type of mangrove mucronata at 3 different stations. The heavy metals tested in this study were zinc ( Zn ) and cadmium ( Cd ). In the highest sediment values for Zn and Cd were 15.516 and 0.532 respectively. In water, the highest levels for Zn and Cd are 0.020 and 0.006 respectively. The highest BCF root values for Zn and Cd are 0.00896 and 0.0609 respectively. The highest leaf BCF values for Zn and Cd are 0.02417 and 0.04487 respectively. The highest TF values for Zn and Cd are 2.68784 and 0.92857 respectively. The Igeo value for Zn is in the unpolluted category and CD is in the slightly polluted category